1999
DOI: 10.1086/302639
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Mutations of the hSNF5/INI1 Gene Predispose to a Variety of Cancers

Abstract: Biallelic, truncating mutations of the hSNF5/INI1 gene have recently been documented in malignant rhabdoid tumor (MRT), one of the most aggressive human cancers. This finding suggests that hSNF5/INI1 is a new tumor-suppressor gene for which germline mutations might predispose to cancer. We now report the presence of loss-of-function mutations of this gene in the constitutional DNA from affected members but not from healthy relatives in cancer-prone families. Furthermore, a constitutional mutation is documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
227
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(245 citation statements)
references
References 35 publications
4
227
1
7
Order By: Relevance
“…These tumors may occur in various organs including kidney, central nervous system (atypical teratoid and rhabdoid tumors, ATRT), liver, skin and soft tissues. The constitutional mutation of hSNF5/ INI1 is associated with a strong predisposition to develop these tumors (Sevenet et al, 1999). Mouse models have confirmed this tumor suppressor role: whereas Snf5/Ini1 homozygous deletion is embryonic lethal, heterozygous mice develop tumors that closely resemble MRTs and that demonstrate loss of heterozygosity of the wild-type allele (Klochendler-Yeivin et al, 2000;Roberts et al, 2000;Guidi et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…These tumors may occur in various organs including kidney, central nervous system (atypical teratoid and rhabdoid tumors, ATRT), liver, skin and soft tissues. The constitutional mutation of hSNF5/ INI1 is associated with a strong predisposition to develop these tumors (Sevenet et al, 1999). Mouse models have confirmed this tumor suppressor role: whereas Snf5/Ini1 homozygous deletion is embryonic lethal, heterozygous mice develop tumors that closely resemble MRTs and that demonstrate loss of heterozygosity of the wild-type allele (Klochendler-Yeivin et al, 2000;Roberts et al, 2000;Guidi et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…Although we were unable to demonstrate that the recombination event directly affected the coding regions of NF2, we nevertheless conclude that both tumours must have a common origin. Several patients with a constitutional INI1 mutation and with two tumours at different sites have been reported (Sevenet et al, 1999b;Savla et al, 2000;Kusafuka et al, 2004;Biegel, 2006;Giunti et al, 2006;Meyers et al, 2006). It will be of interest to determine whether the tumours of these patients, like those of patient III-1, are primary tumours, share somatic changes in the genome, and originate from a common precursor cell as well.…”
Section: Nf2 Rearrangement In the Tumours Of Patient Iii-1mentioning
confidence: 99%
“…Paradoxically, disruption of SWI/SNF function has alternatively been associated with tumorigenesis and lack of cellular/organismal viability. Specifically, loss or mutation of the SNF5/INI1 subunit is associated with rhabdoid tumorigenesis, and it has been convincingly demonstrated that the SNF5/INI1 gene acts as a tumor suppressor (Biegel et al, 1999;Sevenet et al, 1999;Roberts et al, 2002). Correspondingly, diminished expression or loss of Brg1, Brm, Baf57, Baf180, and several other chromatin-modifying genes has been observed in cancer cell lines and tumor specimens (Gregory and Shiekhattar, 2004).…”
Section: Introductionmentioning
confidence: 99%